Shoulder disorders in general practice: prognostic indicators of outcome. - van der Windt, D A (1996)
BACKGROUND: Shoulder pain is common in primary health care. Nevertheless, information on the outcome of shoulder disorders is scarce, especially for patients encountered in general practice. AIM: To study the course of shoulder disorders in general practice and to determine prognostic indicators of outcome. METHOD: For this prospective follow-up study, 11 Dutch general practitioners recruited 349 patients with new episodes of shoulder pain. The participants filled out a questionnaire at presentation and further ones after 1, 3, 6 and 12 months; these contained questions on the nature, severity and course of the shoulder complaints. The association between potential prognostic indicators and the status of shoulder complaints (absence or presence of symptoms) was evaluated after one and 12 months of follow-up. RESULTS: After one month, 23% of all patients showed complete recovery; this figure increased to 59% after one year. A speedy recovery seemed to be related to preceding overuse or slight trauma and early presentation. A high risk of persistent or recurrent complaints was found for patients with concomitant neck pain and severe pain during the day at presentation. CONCLUSION: A considerable number of patients (41%) showed persistent symptoms after 12 months. It may be possible to distinguish patients who will show a speedy recovery from those with a high risk of long-standing complaints by determining whether there is a history of slight trauma or overuse, an early presentation or an absence of concomitant neck pain.